Highly selective oxidation of sulfides on a CdS/C3N4 catalyst with dioxygen under visible-light irradiation. Issue 3 (16th November 2016) - Xu, Yong; Fu, Zi-Cheng; Cao, Shuang; Chen, Yong; Fu, Wen-Fu
Abstract : A CdS/C3 N4 visible-light catalyst exhibits high product selectivity towards photocatalytic oxidation of sulfides into corresponding sulfoxides with dioxygen in methanol. Abstract : A CdS/C3 N4 composite photocatalyst was fabricated by a facile method, and its structure, composition, and morphology were characterized in detail. The catalyst exhibited high photocatalytic product selectivity towards the oxidation of sulfides into corresponding sulfoxides even when the irradiation time was extended to 20 h. The synergistic effect between CdS and C3 N4 gave rise to efficient interfacial transfer of photogenerated electrons and holes on both materials, as confirmed by transient photocurrent measurements. The best photocatalytic activity for the catalyst prepared at 300 °C was achieved at a C3 N4 /CdS ratio of 0.3. Sulfides were efficiently oxidized to sulfoxides with dioxygen under visible-light illumination in methanol at room temperature. The conversion efficiency of sulfides with electron-withdrawing groups was lower than those with a donating substituent, and the conversion strongly depended on the steric hindrance effect of the substituent. A possible photocatalytic mechanism was proposed based on electron spin resonance, trapping experiments, and other experimental results.